LAWS REGARDING PROCURING INTERPRETERS AT THE INQUIRY LEVEL - Taha, Weerayoot (Journal of MCU Nakhondhat, 2021)
The objectives of this research paper were: 1) to study the legal problems related to the procurement of interpreters at the investigative stage; 2) to compare the law relating to the procurement of interpreters in the interrogation stage in Thailand and abroad; 3) to create a law to amend the law on with the provision of an interpreter is a documented research by searching from various documents related It was found that even though there is a Criminal Procedure Code section 13, there are still problems that are not covered, such as the issue of the interpreter’s qualifications, saying that "in the case of unable to speak or understand Thai and without an interpreter", if the parties provide an interpreter themselves, it is considered having an interpreter according to the law. But if you get an interpreter that doesn’t have a good enough interpreter qualification It is deemed that the interpreter does not qualify as an interpreter in the interrogation class. There was a lot of damage in the investigation process. As a result, criminal investigations are unlawful. As for the issue of procuring an interpreter the law only states that the “inquiring officer shall provide an interpreter without delay” does not cover where an interpreter can be obtained or by any means, it must also be completely revised. Compare the laws of each country. Regarding qualifications and provision of interpreters, the United States has a judicial council responsible for defining interpreter qualifications and the court administration is responsible for selecting and certifying English interpreters. Every interpreter must have a criminal background check. Australia There is a code of ethics and an interpreter code of conduct. and has a national interpreter accreditation agency Serves to determine qualifications and certify accreditation as an interpreter. brought to amend the laws of Thailand to be more complete